Darcy Ribeiro e o papel da escola no processo de transformação social - Pereira, Thiago Fernandes dos Santos (2024)
This work rescues Darcy Ribeiro's propositions regarding Brazilian education, focusing on its proposals for the implementation of the Integrated Center for Public Education (CIEP), educational project of which he was the Creator. We seek to understand his conception of education, especially the importance that school education can have as a possible instrument of social transformation. To this end, through bibliographical research, the main works of Darcy Ribeiro that discuss Brazilian society and education are analyzed. Other sources are also analyzed, such as books and academic research regarding Darcy Ribeiro's trajectory, which make it possible to understand his ideas and the historical context in which the author was active. To this end, firstly, a review of the academic production on Darcy Ribeiro's work and proposals is carried out, highlighting those that highlight his work as an educator and educational manager. Subsequently, through his works, we seek to capture his theory and historical explanation regarding the social formation of Brazil. Next, Darcy Ribeiro's criticism is presented in relation to the way in which the process of expansion of public schools in Brazil took place, especially from the 1980s onwards, as well as his divergences in relation to the main social and educational theories of its historical context. We highlight Darcy Ribeiro's proximity to the Escola Nova movement in general and to Anísio Teixeira (1900-1971) specifically and how this proximity contributes to the maturation of his educational proposals. Then, it is presented how Darcy Ribeiro understands the role of education in society, claiming what he understood as an ideal situation. An overview of Darcy Ribeiro's performance and his contribution to the drafting of the current Brazilian Education Law (Law 9,394/1996) is also presented, which suggests some degree of distance between his discourse as an analyst and the compositions inherent to political action. Finally, we present what, within the scope of this work, is considered the main political and educational project developed by Darcy Ribeiro, the CIEPs, insofar as this project, in the hypothesis of this analysis, contributes to elucidating Ribeiro's conception of education, since, as will be demonstrated, most of the propositions of this project dialogue with and are responses to the obstacles to public education diagnosed by Darcy Ribeiro's analyses. We present the characteristics and specificities of this educational project. The conclusions of this work point to the sense that Darcy Ribeiro, through CIEP, invested in education as an element of social transformation from a reformist perspective, however, at the time he developed CIEP's educational ideal, he pointed out that education should promote the modification of students' individual trajectories, deducing that modifications would generate a collective effect on society.